2016
DOI: 10.1177/1049732316658267
|View full text |Cite
|
Sign up to set email alerts
|

User Experience and Care Integration in Transitional Care for Older People From Hospital to Home

Abstract: This meta-synthesis aimed to improve understanding of user experience of older people, carers, and health providers; and care integration in the care of older people transitioning from hospital to home. Following our systematic search, we identified and synthesized 20 studies, and constructed a comprehensive framework. We derived four themes: (1) 'Who is taking care of what? Trying to work together"; (2) 'Falling short of the mark'; (3) 'A proper discharge'; and (4) 'You adjust somehow.' The themes that emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
96
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(104 citation statements)
references
References 40 publications
(290 reference statements)
7
96
0
1
Order By: Relevance
“…However, patients and carers could also be active self‐managers as reflected in the themes: seeking information, discussing and negotiating the transitional care plan, and learning to self‐care. These solution‐oriented themes mirror other research findings . Support from carers and health‐care practitioners and self‐management were emphasized in previous studies about the effectiveness of transitional care interventions with good patient satisfaction ratings and reductions in readmission rates .…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…However, patients and carers could also be active self‐managers as reflected in the themes: seeking information, discussing and negotiating the transitional care plan, and learning to self‐care. These solution‐oriented themes mirror other research findings . Support from carers and health‐care practitioners and self‐management were emphasized in previous studies about the effectiveness of transitional care interventions with good patient satisfaction ratings and reductions in readmission rates .…”
Section: Discussionsupporting
confidence: 73%
“…This theme suggests that regaining independence is an important continuing care need and goal of recovery and supports and expands on findings from other studies. In a meta‐synthesis review, user experience of transitional care was a social process of negotiation and navigation of independence for older people and carers . Other research has also found that independence is important to older people living in the community both with and without support .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature proposes that closer collaboration between various health professionals and facilities is needed to deal with such fragmentation. In addition, studies that explored elderly patients’ admission to EMUs often described their admissions as challenging for both patients and health professionals due to the complex needs of these patients (Allen, Hutchinson, Brown, & Livingston, ; Goodwin et al, ; Gruneir, Silver, & Rochon, ). These problems have also been addressed in a Danish context.…”
Section: Introductionmentioning
confidence: 99%
“…The transitional care of chronic disease patients between hospital and outpatient setting is recognised as a period of vulnerability for patients (Allen, Hutchinson, Brown, & Livingston, 2016;D'Angelo et al, 2014). Discharge planning promotes safe and timely transfers between levels of care and between care settings, by identifying the patient's individual needs and appropriate posthospital discharge destination (Allen et al, 2016;Rodakowski et al, 2017).…”
Section: Introductionmentioning
confidence: 99%